A Case of Plastic Bronchitis - Turgut, Teyfik; In, Erdal; Ozercan, Ibrahim Hanifi; Kaplan, Mustafa (Acad Medical Sciences I R Iran, 2014)
Plastic bronchitis, causing airway obstruction, is a rare condition, especially in adults. In this paper, an adult male. patient with heart failure, viral hepatitis, and a history of previous pneumonia, and-expectorating white, plaque-like secretions-for the last 6 months is presented along with the review of the relevant literature. The material expectorated by the patient was evaluated; macroscopically, this material was observed to be identical to the shape of bronchial branching. Steroid-treatment was commenced after the diagnosis was established, resulting in,the dearly total disappearance of the expectorated material.
Keywords: Children